Compositions Optimization of Antang Corundum for Developing Advanced Ceramic - Olawale Monsur Sanusi; M Dauda; Malachy Sumaila; Abdulkarim S Ahmed; M T Isa; O A Oyelaran; O O Martins (Graduate Program of Syiah Kuala University, 2018)
The research aims to study and optimize the formulation of materials required for advanced ceramic production using response surface methodology (RSM). In this research effort, the five (5) process independent variables studied with their corresponding levels are: Antang corundum powder, A (92.2 – 100 %W); polyvinyl alcohol, B (0 – 5 %W); CaO, C (0 – 2.3 %W); MgO, D (0 – 0.5 %W); and the sintering temperature, E (1200 – 1500 °C). The mechanical property responses determined were density, ρ, compressive strength, C/S, flexural strength, F/S; which are key characteristics of ceramics for armour applications. The optimized density, compressive strength and flexural strength of the sintered Antang corundum are 3.45 g/cm3 g, 1982 MPa and 295 MPa respectively; while the respective RSM prediction values are 3.45 g/cm3 g, 1982 MPa and 295 MPa. On comparing the determined optimum mechanical responses of the sintered Antang ceramic with the maximum RSM prediction values, there is high level of assurance in using RSM for the formulation process in ceramic armour development.